Ethical and Legal Reflections on the Impact of Armed Conflict on Colombian Biodiversity - Bermúdez-Bermúdez, Yonni Albeiro; Sarmiento Ibagué , Silvia Fernanda; Saavedra Ochoa, Johanna Carolina (Scientific journal of social studies, 2024)
The interconnection between armed conflict and biodiversity has revealed significant environmental consequences. The lack of specific legal consideration during and after the conflict has left biodiversity vulnerable, affecting the community as a whole. This article examines the environmental degradation generated by illegal activities and the indiscriminate use of natural resources. One of the main contributors to this damage in our ecosystem is the fumigation strategy to combat drug trafficking. Through qualitative research, the results demonstrate that in the Colombian context, legislation and government policies have the potential to transform the historical relationship towards a more ethical and respectful one. Legal evolution could position the country as a leader in animal protection and environmental sustainability in Latin America. This transformation would not only benefit the environment but also strengthen social cohesion and sustainable development in the country.
Keywords: Armed conflict; environment; animals; biodiversity; sustainability